Measuring and predicting the vapor pressure of gasoline containing oxygenates. (1st May 2019) - Gaspar, Daniel J.; Phillips, Steven D.; Polikarpov, Evgueni; Albrecht, Karl O.; Jones, Susanne B.; George, Anthe; Landera, Alexander; Santosa, Daniel M.; Howe, Daniel T.; Baldwin, Anna G.; Bays, J. Timothy
Highlights: First review of oxygenate vapor pressure measurement and prediction. Specifies vapor pressure measurement methods suitable for use with oxygenates. Reviews methods to predict fuel vapor pressure. Compares many model outputs to measured RVP for real oxygenate-gasoline blends. Abstract: This review describes the measurement and prediction of volatility characteristics, especially Reid vapor pressure, of gasoline blended with oxygenates such as those that could be derived from biomass. Including more advanced biofuels containing oxygen in gasoline affects critical fuel properties related to the volatility of the blended fuel. The vapor pressure of oxygenate-gasoline blends typically exhibits non-ideal behavior requiring updated measurement and prediction tools to ensure the resulting fuel meets all safety and performance specifications. This review, the first covering the measurement, prediction and impact on vapor pressure of oxygenates other than alcohols, discusses the suitability of established methods to measure Reid vapor pressure in blends containing oxygenates. The review then surveys methods used to predict vapor-liquid equilibria along with a description of suitability of these methods for use on gasoline-oxygenate blends. Finally, the outputs of a series of models are compared to Reid vapor pressure measurements for a series of oxygenates in a real gasoline to illustrate the potential and shortcomings of the models.